2015
DOI: 10.1134/s1990519x15010034
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of glucose transporters SGLT1 and GLUT2 with cytoskeleton in enterocytes and Caco2 cells during hexose absorption

Abstract: The distribution of cytoskeleton elements (microtubules and actin filaments) and glucose trans porters SGLT1 or GLUT2 in enterocyte of rat intestine and Caco2 cells during hexose absorption was stud ied. Confocal microscopy revealed that the distribution of SGLT1 and GLUT2 transporters in absorptive cells of the intestinal villus was altered depending on maltose concentration. The transporters were colocal ized with actin. An increased number of vesicles close to microtubules in the apical cell part during abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…It is quite possible that the failure to determine the presence of the GLUT2 transporter in the brush border membrane of enterocytes in the case of a high concentration of glucose in the lumen of the small intestine in mice in the above study is associated with the authors’ use of experimental conditions to which the GLUT2 transporter is sensitive [ 54 ]. Immunohistochemical studies confirmed the incorporation of the GLUT2 transporter into the apical membrane of enterocytes during perfusion of an isolated segment of the jejunum of rats in chronic experiments (in the absence of anesthesia) with a high (75 mM) glucose solution [ 38 , 55 ]. In addition, in a mouse study, increased absorption of α-methyl-D-glucoside (AMG) and the content of the SGLT1 and GLUT2 proteins in the vesicles of the brush border of enterocytes were found in the small intestine 30 min after the glucose gavage.…”
Section: Adaptive Reactions Of Transporters Sglt1 and Glut2 In Physiological Conditionsmentioning
confidence: 92%
“…It is quite possible that the failure to determine the presence of the GLUT2 transporter in the brush border membrane of enterocytes in the case of a high concentration of glucose in the lumen of the small intestine in mice in the above study is associated with the authors’ use of experimental conditions to which the GLUT2 transporter is sensitive [ 54 ]. Immunohistochemical studies confirmed the incorporation of the GLUT2 transporter into the apical membrane of enterocytes during perfusion of an isolated segment of the jejunum of rats in chronic experiments (in the absence of anesthesia) with a high (75 mM) glucose solution [ 38 , 55 ]. In addition, in a mouse study, increased absorption of α-methyl-D-glucoside (AMG) and the content of the SGLT1 and GLUT2 proteins in the vesicles of the brush border of enterocytes were found in the small intestine 30 min after the glucose gavage.…”
Section: Adaptive Reactions Of Transporters Sglt1 and Glut2 In Physiological Conditionsmentioning
confidence: 92%
“…The absorption of glucose may be adjusted by other transporters, such as GLUT2 [ 16 , 17 , 18 ]. Translocation of GLUT2 from cytoplasmic vesicles into the apical membrane markedly increases the capacity of glucose uptake by the enterocyte [ 19 , 20 , 21 ]. Thus, any factor that influences the activities of SGLT1 and GLUT2 will also alter the absorption and metabolism of glucose.…”
Section: Mechanisms Of Glucose Absorption In the Intestinementioning
confidence: 99%
“…A recent study identified that the cytoskeletal components α-tubulin and actin participate in the redistribution of SGLT1 [26 ▪ ,27]. In addition, when caveolin-1, a plasma membrane protein known to regulate the insertion and retrieval of transport proteins, and SGLT1 are coexpressed in oocytes, SGLT1 protein abundance and glucose transport increase [28].…”
Section: Regulation Of Sodium-glucose Cotransportermentioning
confidence: 99%